Lobar Gross Endobronchial Disease Predicts for Overall Survival and Grade 5 Pulmonary Toxicity in Medically Inoperable Early Stage Non-Small Cell Lung Cancer Patients Treated With Stereotactic Body Radiation Therapy - Aghdam, Nima; Lischalk, Jonathan W.; Marin, Monica Pernia; Hall, Clare; O’Connor, Timothy; Campbell, Lloyd; Suy, Simeng; Collins, Sean P.; Margolis, Marc; Krochmal, Rebecca; Anderson, Eric; Collins, Brian T. (Frontiers in Oncology, 2021)
Purpose: SBRT is considered standard of care for medically inoperable ES-NSCLC. Five fraction SBRT approaches have been advocated to mitigate treatment induced toxicity. In this report, we examine the mature clinical outcomes of a diverse cohort of ES-NSCLC patients with both peripheral and central tumors treated with a conservative 5 fraction SBRT approach and evaluate the role of lobar gross endobronchial disease (LGED) in predicting overall survival and treatment-related death. Method: Medically inoperable biopsy-proven, lymph node-negative ES-NSCLC patients were treated with SBRT. Bronchoscopy was completed prior to treatment in all centrally located cases. The Kaplan-Meier method was used to estimate OS, LC, RC, DMFS and DFS. OS was stratified based on clinical stage, histology, tumor location and LGED. Toxicities were scored according to the CTCAE 5.0. Results: From December 2010 to December 2015, 50 consecutive patients were treated uniformly with a 50 Gy in 5 fraction SBRT approach (tumor BED10 ≥ 100 Gy) and followed for a minimum of 5 years or until death. At a median follow up of 42 months for all patients, 3-year OS was 50%. Three-year OS did not statistically differ between stage I and stage II disease (51% vs. 47%; p=0.86), adenocarcinoma and squamous cell carcinoma (50% vs. 45%; p=0.68), or peripheral and central tumors (56% vs. 45%; p=0.46). Five central tumors were found to have LGED, and 3-year OS for this cohort was quite poor at 20%. Cox regression analysis identified LGED as a predictor of OS while controlling for age, stage and location (OR:4.536, p-value=0.038). Despite the relatively low dose delivered, treatment likely contributed to the death of 4 patients with central tumors. Lobar gross endobronchial disease was an independent predictor for grade 5 pulmonary toxicity (n=4, p=0.007). Specifically, 3 of the 5 patients with LGED developed fatal radiation-induced bronchial stricture. Three-year LC, RC, DMFS and DFS results for the group were similar to contemporary studies at 90%, 90%, 82% and 65%. Central location of ES-NSCLC is a well-established predictor for severe SBRT-related toxicity. Here we identify LGED as a significant predictor of poor overall survival and grade 5 pulmonary toxicity.